Art, artisans & apprentices : apprentice painters & sculptors in the early modern British tradition - Ayres, James (Oxbow Books, 2014)
Before the foundation of academies of art in London in 1758 and Philadelphia in 1805, most individuals who were to emerge as artists trained in workshops of varying degrees of relevance. Easel painters began their careers apprenticed to carriage, house, sign or ship painters, whilst a few were placed with those who made pictures. Sculptors emerged from a training as ornamental plasterers or carvers. Of the many other trades in a position to offer an appropriate background were 'limning', staining, engraving, surveying, chasing and die-sinking. In addition, plumbers gained the right to use oil.